Strategi Pengembangan Usaha Kepiting di Desa Prapag Kidul, Kec. Losari, Kab. Brebes : Analisis Manajemen Strategi - Risma Al-fain; Saefullah Saefullah (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2025)
Crab farming in Prapag Kidul Village has significant potential to support the local economy. However, challenges such as price fluctuations, capital limitations, and traditional marketing approaches hinder business growth. This research aims to analyze crab farming business management strategies using a strategic management approach, including planning, implementation, and evaluation of business strategies. The research employed a qualitative approach through in-depth interviews and field observations. Results indicate that effective strategies include product diversification, digital marketing, cooperative partnerships, and financial management optimization. Synergy between crab farmers, government, and business stakeholders is necessary to enhance competitiveness and sustainability of the crab industry in this region. The study reveals that crab production in Prapag Kidul has increased by 31.6% over the past five years, while production value grew by 84.2%, demonstrating significant growth potential despite identified constraints in implementation.